Evaluation of asymmetric dimethylarginine as an inflammatory and prognostic marker in dogs with acute pancreatitis. (7th May 2020) - Gori, Eleonora; Pierini, Alessio; Lippi, Ilaria; Meucci, Valentina; Perondi, Francesca; Marchetti, Veronica
Abstract: Background: Asymmetric dimethylarginine (ADMA) has been proposed as a severity marker in humans with acute pancreatitis (AP). Objectives: To evaluate ADMA in dogs with AP compared with healthy dogs and its association with severity of disease, mortality, and indicators of the systemic inflammatory response syndrome (SIRS), including serum C‐reactive protein (CRP) concentration, WBC count, and band neutrophils. Animals: Fifty‐four dogs with AP and a control group (CG) of 28 healthy dogs. Methods: Cohort study including dogs with AP diagnosed using clinical and laboratory variables, abnormal canine pancreatic lipase (cPL) concentration, and compatible abdominal ultrasound examination findings performed within 48 hours of admission. Canine AP severity (CAPS) was calculated. Serum concentration of ADMA was measured using high performance liquid chromatography. Blood donor‐, staff‐, and student‐owned dogs were enrolled in the CG. Results: Dogs with AP had higher median admission serum ADMA concentrations compared with the CG (62 versus 48.5 μg/dL; P = .003). Dogs with CAPS ≥11 had higher serum ADMA concentrations than did dogs with CAPS <11 (92 versus 54.6 μg/dL P = .009). Univariable analysis for mortality, CAPS score, band neutrophils, CRP, and ADMA were included in multivariable logistic regression, in which only ADMA was associated with mortality ( P = .02). Survivors had a significant decrease in ADMA at first reevaluation compared to admission ( P = .02). Conclusions and Clinical Importance: Because serum ADMA concentrations were higher in AP dogs compared with the CG, it may have value as a biomarker in the diagnosis of AP in dogs. In addition, because ADMA was associated with mortality, it may have prognostic value.